PARADIGMA MASYARAKAT TERHADAP ASURANSI SYARIAH - Nurma Sari (Jurnal Investasi Islam, 2017)
No one of God’s creatures is able to predict a future event appropriately, even with the use of analytical methods and advanced tools. This is because everything that will happen in the future will in principle be full of uncertainty followed by various risks in it. In an increasingly advanced era with all the complex issues, insurance comes to improve itself and grow better with the various innovations that run. Along with its progress also shifts social values which is the initial concept of insurance. Where insurance has now turned a face into a business-laden institution by prioritizing profit. So if we look at the insurance that runs like a business institution (conventional insurance) from the eyes of sharia, it is clear that it is prohibited in Islam because it contains gharar, Maisir and indications of usury. But it is still not able to open the eyes of Indonesian people who notabenenya muslim to switch to oriented on Takaful insurance. This paper aims to describe the problems in Takaful insurance that makes the paradigm of the community is reluctant (less interested) Takaful insurance and follow-up what needs to be done to seek Sharia insurance a priority of the community when it wants to minimize risk in accordance with Islamic religious teachings.